(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Dental composites have emerged as indispensable materials in modern dentistry, offering versatile solutions for restorative and cosmetic procedures. Composed of a resin matrix, inorganic fillers, and various additives, dental composites closely mimic the natural appearance of teeth while providing excellent mechanical properties and adhesive bonding to dental tissue. This abstract provides a concise overview of dental composites, highlighting their composition, properties, applications, and significance in clinical practice.